Resistance of cotton varieties to Spodoptera frugiperda (Lepidoptera: Noctuidae) - Jesus, Flavio Goncalves de; Boica Junior, Arlindo Leal [UNESP]; Silva Alves, Gleina Costa; Busoli, Antonio Carlos [UNESP]; Zanuncio, Jose Cola (Soc Colombiana Entomologia-socolen, 2014)
The fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae) is a polyphagous pest species of cultivated plants. Changes in cotton crop systems are increasing the importance of this pest in cotton in the El Cerrado region of Brazil. This work aimed to evaluate resistance types of cotton (Gossypium hirsutum) varieties by non-preference to oviposition and feeding along with antibiosis to S. frugiperda in the laboratory (27 +/- 2 degrees C, 70 +/- 10% R.H. and photophase of 14 h). Two tests were performed to evaluate the non-preference to oviposition and feeding, one with free choice in a randomized block design and another in a completely randomized design. Leaves of the cotton varieties DeltaOpal (R), NuOpal (R), FMX 993 (R), FMT 701 (R), FMX 910 (R) and FMX 996 (R) were offered daily to S. frugiperda larvae. The presence of antibiosis was evaluated by the duration of each instar and of the larval and pupal stages, larval and pupal biomass, and adult longevity and fecundity. The NuOpal (R) variety was the most resistant to S. frugiperda. Spodoptera frugiperda fed on non-Bt cotton had heavier pupae and larvae, shorter development time for the larval stage, longer adult longevity, and a higher rate of oviposition and total viability when compared to the Bt cotton varieties.
Keywords: Fall armyworm; Gossypium hirsutum; Plant resistance